P587 Quality of care indicators in inflammatory bowel disease: local pilot study. (25th January 2019) - Sarraj, R; Bravo, F; Maude, M; Macpherson, A; Juillerat, P
Abstract: Background: Recommendations have been established for an optimal care of inflammatory bowel disease (IBD) patients. 1–3 The aim of this study was determine whether patients were receiving appropriate care. Methods: 40 consecutive patients with IBD from the outpatient Clinic of Bern University Hospital with at least 2 years of follow-up were retrospectively included in this pilot study. Clinical, laboratory and endoscopic data were collected from the patient files. Frequency of surveillance measures such as metabolic bone disease prevention, colon cancer and dermatological screening were also considered. Results: The study population consisted of 40 patients 30 with Crohn's disease, 10 with ulcerative colitis (UC). 60% of patients with distal UC were receiving topical aminosalicylate therapy and oral aminosalicylates were appropriately dosed in 86% of the case. Unfortunately, 73% of patients have been treated with corticosteroids for longer than 3 months, however 96% of patient there was an attempt to start steroid sparing medications (azathioprine /6MP, MTX, Anti-TNF agents). Of the patients treated with either 6MP or AZA 75% were appropriately dosed. 78% of patient received adequate treatment to prevent metabolic bone disease. 90% of patients meeting indications for surveillance colonoscopy for dysplasia could undergo colonoscopy at the appropriate interval. 60% of patient did undergo a dermatological screening at least every 2 years. Conclusions: According to current guidelines, there is room for improvement in the management of IBD patients. In particular, for the use of corticosteroids. In all other criteria, a satisfactory proportion of patients met the conditions for quality of care. A larger retrospective study, with extended criteria and clinical outcome analysis is required to build a valuable structure for quality assessment of our daily clinical practice. References 1. Reddy SI, Am. J. Gastro. 2005, Jun 100(6): 1357–61. 2. Harbord M, J. Crohns Colitis. 2017, Jul 1;11(7): 769–784. 3. Fernando Gomollón, J. Crohns Colitis. 2017 Jan 11(1): 3–25